Mutagenic specificity in reovirus. - Ray, U R (1979)
Mutagenic specificity in response to chemical mutagens has been observed with certain temperature-sensitive mutants of reovirus type 3. One mutant induced by nitrous acid reverted specifically with nitrous acid. Three nitrosoguanidine-induced mutants reverted after nitrous acid treatment. These findings thus suggest that analysis of chemical induction of reversion from the temperature-sensitive phenotype may be a useful approach for studying the nature of mutation in animal viruses.